2010
DOI: 10.1037/a0021527
|View full text |Cite
|
Sign up to set email alerts
|

On consumer advocacy and the diagnosis of mental disorders.

Abstract: This article provides a brief overview of the development of consumer and family advocacy activity during the past 40 years, mentioning the involvement of these groups in the treatment and research arenas and describing a dearth of such activities related to matters of diagnosis. In an attempt to address this relative inattention to diagnostic issues, the article continues by proffering a relative personal account and then reporting the results of a quasi-qualitative study that collected opinions about the dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 15 publications
0
19
0
Order By: Relevance
“…In some countries such heavily stigmatized associations have been seen as sufficiently important as to require a disorder being renamed, by national fiat (Sato, 2006 It is not uncommon for the service user to disagree with the diagnosis they are given. Both family members and service users report at times that the diagnosis did not match their interpretation of their experience, and came with too many negative associations to be accepted (Frese and Myrick, 2010;Moeke-Maxwell et al, 2008;Laird et al, 2010). Some felt that clinicians did not communicate with them in a way that allowed hope for the prospect of future health.…”
Section: Significance Of Diagnosis To the Service User And Their Commmentioning
confidence: 99%
See 4 more Smart Citations
“…In some countries such heavily stigmatized associations have been seen as sufficiently important as to require a disorder being renamed, by national fiat (Sato, 2006 It is not uncommon for the service user to disagree with the diagnosis they are given. Both family members and service users report at times that the diagnosis did not match their interpretation of their experience, and came with too many negative associations to be accepted (Frese and Myrick, 2010;Moeke-Maxwell et al, 2008;Laird et al, 2010). Some felt that clinicians did not communicate with them in a way that allowed hope for the prospect of future health.…”
Section: Significance Of Diagnosis To the Service User And Their Commmentioning
confidence: 99%
“…(Frese and Myrick, 2010) However, over time Myrick found that more diagnoses were added, and some were changed. As the "labels" shifted towards words that tend to be used derogatorily in the popular media, and were prefaced by descriptors such as "persistent", "life-long" and "devastating", her first response could not be maintained.…”
Section: "…The Diagnosis Provided Me With Information About What Was mentioning
confidence: 99%
See 3 more Smart Citations